Intra-abdominal infections survival guide: a position statement by the Global Alliance For Infections In Surgery - Sartelli, Massimo; Barie, Philip; Agnoletti, Vanni; Al-Hasan, Majdi N; Ansaloni, Luca; Biffl, Walter; Buonomo, Luis; Blot, Stijn; Cheadle, William G; Coimbra, Raul; De Simone, Belinda; Duane, Therese M; et al. (World journal of emergency surgery, 2024)
Intra-abdominal infections (IAIs) are an important cause of morbidity and mortality in hospital settings worldwide. The cornerstones of IAI management include rapid, accurate diagnostics; timely, adequate source control; appropriate, short-duration antimicrobial therapy administered according to the principles of pharmacokinetics/pharmacodynamics and antimicrobial stewardship; and hemodynamic and organ functional support with intravenous fluid and adjunctive vasopressor agents for critical illness (sepsis/organ dysfunction or septic shock after correction of hypovolemia). In patients with IAIs, a personalized approach is crucial to optimize outcomes and should be based on multiple aspects that require careful clinical assessment. The anatomic extent of infection, the presumed pathogens involved and risk factors for antimicrobial resistance, the origin and extent of the infection, the patient's clinical condition, and the host's immune status should be assessed continuously to optimize the management of patients with complicated IAIs.
Keywords: rizikové faktory; Intraabdominal Infections; Humans; Anti-Bacterial Agents; lidé; antibakteriální látky; nitrobřišní infekce; Risk Factors